PERAN PEMERINTAH UNTUK MENCAPAI TUJUAN BANGSA DENGAN PEMANFAATAN TEKNOLOGI - Nurrahman, Agung (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
There are three primary aims of this paper. Firstly, it is to analyse proper role theory, especially in government sector. Secondly, this study would examine the role of Indonesian government, according to relevant role theory, in order to achieve nation’s goal. Thirdly, this paper would examine the use of technology by Indonesia government in order to achieve that goal. Furthermore, this research using qualitative data collecting methods with descriptive approach and case study strategy. There are some findings of this study. First, there are four main elements in the theory aspect of the role of the government, especially in Indonesia, namely: One, the political and social contract. Two, the process of deliberation or formulation of public policy that becomes the main point before entering into other points as derivatives. Three, the concept of implementation of public policy, in which there is a dimension of rights and obligations, both for the government and society, as both parties agree on social and political contracts, where both aspects become the fourth and fifth points. Secondly, the Indonesian government's policy in case studies that researchers use, namely the issue of radicalism, is considered to be contrary to the contract value of the nation and state. This can be further seen in pancasila related to national unity and unity and social justice. Furthermore, the dynamics of the issue are also contrary to the vision of the ministry of religion, in terms of maintaining intra-religious harmony. Even in the process of drafting a Joint Decree of the ministry related to this issue, not through an appropriate process of public policy formulation. Thirdly, even if the policy must be taken by the government, it is necessary to take appropriate public policy formulation measures. Moreover, it is beyond the vision and mission of the ministry, campaign promises and the constitution. Therefore, one of the efforts that must be taken to produce good public policy is to provide public spaces availability to participate in the formulation. Where in this case, technology, especially the presence of virtual space as an extension of physical space, has a big part in that. Unfortunately the government does not provide access for the public in this virtual space, and seems to separate certain spaces which creating divsion of personality. Keywords: The role of government, the theory of the role of government, technology.